The Asymmetrical Effect of Polarization on Support for Independence: The Case of Catalonia - Juan Rodríguez-Teruel; Astrid Barrio (Politics and Governance, 2021)
The article analyses the consequences of elite polarization at the mass level in the centre-periphery dimension. We analyse the rapid rise in support for independence in Catalonia, focusing on the role of party competition around the centre-periphery cleavage. We argue that mainstream actors’ adoption of centrifugal party strategies with respect to the national question produced a polarizing dynamic in the party system that eventually caused voters’ attitudes regarding the centre-periphery issue to harden. Indeed, we posit that this increase in mass polarization was a consequence of party agency that subsequently helped to drive attitudes regarding independence. To test this hypothesis, we measure centre-periphery polarization (as perceived by voters) by adopting two different perspectives—inter-party distances (horizontal polarization) and party-voter distances (vertical polarization)—and then run logistic regressions to explain support for independence. The findings show an asymmetrical effect on polarization. While the centrifugal strategy implemented by Catalan regionalist parties paved the way for a radicalization of voters on the Catalan nationalist side, among voters for non-regionalist parties, attitudes towards independence were initially less conditioned by this polarization. The results provide evidence of the political effects of elite polarization.